Factors influencing the degree of physician-pharmacists collaboration within governmental hospitals of Jigjiga Town, Somali National Regional State, Ethiopia, 2020 - Workineh Diriba Gemmechu; Endalkachew Mekonnen Eticha (BMC, 2021)
Abstract Background Collaboration is the way to deliver the desired health outcome for the patients or service users in the healthcare. Inter-professional collaboration can improve medication safety, patient outcome and minimize healthcare costs. This study aimed to explore the degree of collaboration and factors influencing collaboration between physicians and pharmacists within the public hospitals of Jigjiga town, Somali National Regional State, Ethiopia, 2020. Methods A cross-sectional study qualitative was conducted among 149 participants in the two governmental hospitals of the Jigjiga town with a response rate of 79.87%. The collaborative working relationship model and the physician-pharmacist collaborative instrument with three main exchange domains (trustworthiness, role specification, and relationship initiation) and collaborative care items were used. An independent sample t-test was used to compute the differences of the mean scores of physician-pharmacist collaborative instrument domains and collaborative care. Separate multiple regression was employed to assess factors influencing collaborative care for pharmacists and physicians. Results This study showed that pharmacists reported higher mean of collaborative care (10.66 ± 4.75) than physicians (9.17 ± 3.92). The multiple regression indicated that area of practice influence both professionals' collaborative practice. A significant association between collaborative care and the two PPCI domains (trustworthiness and relationship initiation for the physicians; role specification and relationship initiation for pharmacists) was established. Conclusions The study showed that the collaboration between the physicians and pharmacists was sub-optimal and the exchange variables had a significant influence on their collaboration. Recommendation Physicians and pharmacists need to exert more efforts to enhance this collaboration. Further qualitative study might be needed to search for factors affecting, barriers and how to develop collaborative practice.